Shifting the US-Myanmar under Trump Administration and its Geopolitical Implication - Thu Htet (WIMAYA, 2021)
This paper aims to analyze the shifts in the US-Myanmar relations during Trump administration compared to that of Obama administration, what factors affect such shifts, and how they posit important geopolitical implication. Under Trump administration, the US-Myanmar relations largely revolved around the Rohingya crisis, which shaped the relations between the two nations ‘substantially uncomfortable’. The factors affecting the changing relationship are the temporal dimension of Rohingya crisis, civil-military relations under NLD government, as well as Trump’s ‘American First’ foreign policy, which contributed to the declining of strategic engagement towards Indo-Pacific region where Myanmar is located. This caused an important geopolitical implication: the growing Chinese influence in Myanmar.